Effect of raja yoga meditation on glycaemic status in type 2 diabetes mellitus - Phatak, Mrunal S.; Chawla, Tara G.; Phatak, Pallavi S. (International Journal of Research in Medical Sciences, 2017)
Background: In this modern era stress is a commonly seen phenomenon. Stress affects physiological equilibrium leading to many pathologic conditions including endocrine disorders like diabetes mellitus. Physiological responses to stress including increased glucose production, glucose mobilisation and insulin resistance could partially mediate this risk. Meditation is a behavioural phenomenon which can be used to cause autonomic nervous system alterations and help in reducing stress and its effects. Methods: In this cross-sectional study 60 patients of type 2 diabetes mellitus (T2DM) were divided into 2 groups, 30 patients who are practicing Raja yoga meditation for more than 5 years and their glycemic status was compared with the glycemic status of 30 patients of T2DM who did not practice any form of yogic meditation. Results: Blood glucose level and glycated haemoglobin levels were significantly lower in yoga practitioners. Lipid profile showed significant reduction in total cholesterol and serum triglycerides. Conclusions: Thus, a better glycaemic control is achieved with regular practice of Raja yoga meditation which helps in maintaining optimal level of autonomic equilibrium at rest as well as during exposure to stress.